A study on mefloquine-associated neuropsychiatric manifestations among Nepalese soldiers posted for United Nations peace mission - Katuwal, Nagendra; Khatri, Devendra; Shrestha, Dhan Bahadur; Dhungel, Omkar; Oli, Prakash Raj; Aryal, Barun Babu; Rawal, Namrata; Rana, Kishor JB; Manandhar, Pradeep; Panta, Chiranjibi (Journal of Kathmandu Medical College, 2018)
Background: Mefloquine is one of the prophylactic medications recommended by the government of Nepal. In areas of intense malaria transmission, prophylaxis with drugs is an important strategy to prevent malaria. During prophylactic use, several neuro-psychiatric and other systemic adverse effects can occur with mefloquine. Notable psychiatric manifestations include anxiety, depression, restlessness, and confusion. Objective: To study the psychiatric effects of mefloquine in Nepalese serving soldiers posted in the United Nations peace mission nations of the African continent taking mefloquine prophylaxis. Methodology: This prospective descriptive study was conducted among Nepalese soldiers posted for United Nations peace mission in South Sudan over a period of one year. Soldiers of age group 25-55 years posted for peace mission having no past and family history of psychiatric illnesses were enrolled in the study. General Health Questionnaire-12, translated into Nepali by Nepalese Journal of Psychiatry, with a questionnaire about the side effects was used to collect detailed information. Results: A total of 524 soldiers posted on peace mission were enrolled in the present study, among which 520 were male and four were female. There were four positive cases with General Health Questionnaire score 3/12 or more. Among the adverse events noted, neuropsychiatric adverse events were more common than non-neuropsychiatric adverse events but none were of life-threatening severity. Conclusion: In a malaria endemic region with a high prevalence of malaria, mefloquine can be safely used in an apparently healthy population, judging the risk-benefit.